Semitransparent CH3NH3PbI3 Films Achieved by Solvent Engineering for Annealing‐ and Electron Transport Layer‐Free Planar Perovskite Solar Cells. Issue 6 (30th March 2018) - Wei, Xiangfeng; Zhang, Mengmeng; Liu, Xiaoqian; Chen, Fang; Lei, Xunyong; Liu, Han; Meng, Fancheng; Zeng, Hualing; Yang, Shangfeng; Liu, Jiehua
Abstract : A new solvent engineering method by using toluene as an antisolvent is developed to construct dense, mirror‐like, void‐free, and semitransparent CH3 NH3 PbI3 (MAPbI3 ) perovskite films, and the corresponding planar heterojunction perovskite solar cells (PSCs) exhibit a power conversion efficiency (PCE) of 16.1%. Upon removing the commonly used TiO2 electron transport layer (ETL), a PCE of 12.6% is attained for such an ETL‐free PSC device, suggesting the superior electron self‐extraction ability of MAPbI3 perovskite film fabricated via our approach. Moreover, we further simplified the device fabrication process by removing the thermal post‐annealing step, which is generally required for conventional one‐step or two‐step solution methods used for preparing perovskite films, and achieved a PCE of 13.0 and 10.5% for the PSCs with ETL and without ETL, respectively. Thus, the mirror‐like and semitransparent MAPbI3 perovskite films prepared via our approach can be prepared without thermal annealing process, and this provides a new strategy for solar cells based on non‐FTO substrates and with tandem structures. Abstract : A new solvent engineering method by using toluene as an antisolvent is developed to construct dense, mirror‐like, void‐free, and semitransparent CH3 NH3 PbI3 perovskite films. The corresponding planar heterojunction perovskite solar cells exhibit a power conversion efficiency (PCE) of 16.1%. Upon removal of TiO2, >10% PCE is still attained, revealing that the CH3 NH3 PbI3 perovskite film possesses good electron self‐extraction ability.